2013
DOI: 10.1080/10810730.2013.825672
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Adherence: A Health Literacy–Informed Model of Medication Self-Management

Abstract: Medication adherence has received a great deal of attention over the past several decades; however, its definition and measurement remain elusive. The authors propose a new definition of medication self-management that is guided by evidence from the field of health literacy. Specifically, a new conceptual model is introduced that deconstructs the tasks associated with taking prescription drugs; including the knowledge, skills and behaviors necessary for patients to correctly take medications and sustain use ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 52 publications
3
101
0
1
Order By: Relevance
“…Taking medications is a multi-step process and requires filling the prescription, understanding the drug regimen, organizing and taking the medication as directed, tolerating any side effects and then continuing the medication over the longterm [8]. This process may break down at any point; 24% of new prescriptions are never filled [9], 50% of patients do not take medication as directed [10], and (with statin medication for hypercholesterolemia, for example) 25-50% stop taking the medication after one year and 75% after two years [11].…”
Section: Discussionmentioning
confidence: 99%
“…Taking medications is a multi-step process and requires filling the prescription, understanding the drug regimen, organizing and taking the medication as directed, tolerating any side effects and then continuing the medication over the longterm [8]. This process may break down at any point; 24% of new prescriptions are never filled [9], 50% of patients do not take medication as directed [10], and (with statin medication for hypercholesterolemia, for example) 25-50% stop taking the medication after one year and 75% after two years [11].…”
Section: Discussionmentioning
confidence: 99%
“…Koh et al and Bailey, Oramasionwu, and Wolf added some of the clinical benefits linked to health literacy interventions include: reduced mortality; improved patient adherence to medical instructions; and overall patient safety [21,60]. In a summary of research findings, the National Network of Libraries of Medicine noted health literacy interventions therapeutically assisted patients with cancer, diabetes, asthma, and hypertension [9].…”
Section: Health Literacymentioning
confidence: 99%
“…This is also consistent with Hardon et al, (2006) who reported 77% in sub-Sahara Africa. Bailey, Oramasionwu, & Wolf, [7], also noted that patient's failure in maintaining dose time and schedule contributed to poor adherence which was reported at 56.8%. Some studies have also documented challenges facing AIDS patients in adhering to ART and its implications for multiple poor health outcomes such as drug resistance [4], high rate of relapse and rehospitalization [6], co-morbidities with other diseases [7], high mortality and increased global burden of the disease [11].…”
Section: Introductionmentioning
confidence: 98%